Exchange rate expectations of chartists and fundamentalists - Christian D. Dick; Lukas Menkhoff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper provides novel evidence on exchange rate expectations of both chartists and fundamentalists separately. These groups indeed form expectations differently. Chartists change their expectations more often; however, all professionals' expectations vary considerably as they generally follow strong exchange rate trends. In line with non-linear exchange rate-modeling, professionals expect mean reversion only if exchange rates deviate much from PPP. Chartists survive in FX markets as they forecast equally accurately as fundamentalists. Unexpected from an efficient market viewpoint, chartists even outperform fundamentalists at short horizons. Overall, these findings clearly support the chartist-fundamentalist approach.
urn:nbn:de:bsz:180-madoc-322360
Keywords: F31; G15; D84; 330; exchange rate formation; expectation formation; heterogeneous agent models; forecasting performance